Analisis Strategi Guru dalam Menciptakan Pembelajaran Aktif dan Bermakna di SD Negeri 81 Palembang - M. Hilman Hibatullah; Putri Zalwa Sairua; Chandara Kinasih Sekarwari; Abdilla Afza Hinaya (Advances In Education Journal, 2026)
This study analyzes the strategies used by teachers to create active and meaningful learning for fifth-grade students at SD Negeri 81 Palembang. The background of this research is the phenomenon of passive, teacher-centered learning that reduces student motivation and understanding of concepts. This study aims to identify teacher strategies, describe their implementation, analyze supporting and inhibiting factors, and evaluate the effectiveness of these strategies in creating active and meaningful learning. The method used is a descriptive qualitative approach with data collection techniques including observation, in-depth interviews, and documentation. The results showed that teachers at SD Negeri 81 Palembang used various strategies such as project-based learning, inquiry-based learning, cooperative learning models (STAD and Jigsaw), and the use of interactive learning media. These strategies increased student participation, critical thinking skills, collaboration, and understanding of concepts. Supporting factors include school facilities and teacher training, while inhibiting factors include time constraints and students’ diverse abilities. The conclusion is that teachers’ strategies are effective in creating active and meaningful learning, and collaboration between teachers, schools, and parents is essential for optimization.